Spectroscopy with Three-Dimensional Model Atmospheres of Late-Type Stars. Issue Volume 11:Issue A29B(2015) (27th October 2016) - Collet, Remo
Abstract: In this contribution, I present the results of a differential analysis of CH spectral lines for the determination of carbon abundances with three- and one-dimensional model atmospheres of late-type stars at various metallicities. 3D-1D abundance corrections are found to be significant particularly at low metallicities and for turn-off stars. The dependence of 3D-1D carbon abundance corrections on the stellar C/O ratio is also discussed.